2017
DOI: 10.1039/c7py00844a
|View full text |Cite
|
Sign up to set email alerts
|

Radical polymerization in the presence of a peroxide monomer: an approach to branched vinyl polymers

Abstract: In this paper, we report radical polymerization in the presence of a peroxide monomer for the preparation of branched vinyl polymers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 57 publications
1
26
0
Order By: Relevance
“…It was previously reported that peroxides can be employed for crosslinking of polymers [18][19][20][21][22]. Their main advantages as crosslinking agents are the (1) ability to crosslink saturated and unsaturated polymers, (2) high-temperature resistance, (3) good elastic behavior at higher temperature, (4) low moisture uptake, and (5) no staining or discoloration of the resulting products.…”
Section: Introductionmentioning
confidence: 99%
“…It was previously reported that peroxides can be employed for crosslinking of polymers [18][19][20][21][22]. Their main advantages as crosslinking agents are the (1) ability to crosslink saturated and unsaturated polymers, (2) high-temperature resistance, (3) good elastic behavior at higher temperature, (4) low moisture uptake, and (5) no staining or discoloration of the resulting products.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, LCHBPs can also be easily afforded through certain copolymerizations by using high molecular weight macromonomers or small molecular monomers, or simultaneously both, as building blocks via A 2 + B x ( x ≥ 3) or AB + AB x ( x ≥ 2) copolymerization process . Additionally, the famous self‐condensing vinyl polymerization (SCVP) usually affording conventional HBPs with short subchains has been adjusted for the preparation of LCHBPs through copolymerization of the traditional small molecular inimer with an additional comonomer, or direct homopolymerization of a macroinimer …”
Section: Introductionmentioning
confidence: 99%
“…The successive initiation and polymerization of the formed macromolecular reducing agent and macromonomer will generate branching structure. We note that RAM can really form two kinds of radicals: >N‐CH • ‐CH 2 ‐CH 2 ‐ (signal g at about chemical shift 2.6 ppm) and >N‐CH 2 • (at about chemical shift 3.0 ppm), indicating that the polymerization functionality of the RAM may be larger than 3, which is quite different from CTM and peroxide monomer, implying that this polymerization system may be easy to suffer from gelation compared to that reported in the literature, where the polymerization functionality of the CTM and the peroxide monomer is usually 3 . Correspondingly, branched polymers with moderate branching degree can be prepared at low branching monomer dosage.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, whereas Michael addition occurs between the –SH group and the vinyl group during storage and polymerization of CTM, it does not contribute to the branching. To solve these drawbacks, a peroxide monomer t ert‐butyl peroxyacetate (BPAMA) have been designed to prepare branched vinyl polymers through radical polymerization under solvent‐free conditions, which makes the preparation of branched vinyl polymers almost equally as simple as those of their linear analogs . Nevertheless, the polymerization still suffers from gelation at high BPAMA concentration, the reaction system must be introduced in DDT controlling the primary chain length and preventing gelation, results in the formation of branched polymers with low molecular weights and board polydispersities because of chain‐transfer reaction.…”
Section: Introductionmentioning
confidence: 99%